Peran guru dalam mengembangkan psikomotorik anak usia dini melalui media pembelajaran outing class - Aisyatin Kamila; Rizki Hidayaturrochman (PSYCOMEDIA : Jurnal Psikologi, 2022)
Psychomotor development is an important thing to develop, one of its functions is to strengthen the fine and gross motor skills of a child. This study aims to describe in depth an overview of the teacher's role in developing psychomotor early childhood through outing class learning. This study uses descriptive qualitative research methods using research instruments in the form of observation sheets, documentation and interviews. The results showed that: Outing class activities were quite effective in optimizing children's psychomotor development. Outing class activities are carried out with outbound activities. The location of the outbound implementation is near the school and outside the school. Aspects developed in the psychomotor game include developing the value of hard work, independence, quick thinking, and early childhood cooperation.